ILRI research on forages - Helping farmers produce more - Jorge, M.A.B. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Alexandra Jorge, reflects on ILRI's forage research and the importance of the forage seeds genebank hosted at ILRI in Addis Ababa, Ethiopia.